In vitro study to assess the efficacy of CDK4/6 inhibitor Palbociclib (PD‐0332991) for treating canine mammary tumours. (12th July 2019) - Schoos, Alexandra; Knab, Vanessa M.; Gabriel, Cordula; Tripolt, Sabrina; Wagner, Daniela A.; Bauder, Barbara; Url, Angelika; Fux, Daniela A.
Abstract: Therapy of canine mammary tumours (CMTs) with classical antitumour drugs is problematic, so better therapeutic options are needed. Palbociclib (PD‐0332991) is an innovative and effective anticancer drug for the treatment of breast cancer in women. Palbociclib is an inhibitor of cyclin‐dependent kinase 4 (CDK4) and CDK6, which are key regulators of the cell cycle machinery and thus cell proliferation. In the present in vitro study, we investigated whether Palbociclib also represents a candidate drug to combat CMT. For this purpose, the effect of Palbociclib was analysed in P114 and CF41 cells, two CMT cell lines with an endogenous CDK4/6 co‐expression. Incubation of P114 and CF41 cells with Palbociclib resulted in a dose‐ and time‐dependent loss of phosphorylated retinoblastoma protein (pRb), a classical CDK4/6 substrate within the cell cycle machinery. Moreover, treatment of CMT cells with Palbociclib‐induced cell cycle arrest affected cell viability, prevented colony formation and impaired cell migration activity. Palbociclib also inhibited the growth of P114 and CF41 cell spheroids. Immunohistochemical analysis of canine patient samples revealed a consistent expression of CDK6 in different canine mammary carcinoma types, but an individual and tumour‐specific expression pattern of phosphorylated pRb independent of the tumour grade. Together, our findings let us suggest that Palbociclib has antitumour effects on CMT cells and that canine patients may represent potential candidates for treatment with this CDK4/6 inhibitor.